The SARS-CoV-2 main protease causes mitochondrial dysfunction in a yeast model - Wojciech Grabiński; Anna Kicińska; Karolina Funtowicz; Tomasz Skrzypczak; Andonis Karachitos (Scientific Reports)
Abstract Saccharomyces cerevisiae has proven to be an invaluable model organism for studying mitochondrial function owing to its genetic tractability and the high conservation of mitochondrial processes among eukaryotes, including humans. Yeasts are easy to culture and manipulate genetically, which allows rapid generation of mutant strains and detailed dissection of mitochondrial pathways. In addition, the ability of yeasts to survive without functional mitochondria allows the study of mutations that are lethal to organisms that are dependent on aerobic metabolism. Taking advantage of these benefits, we investigated the toxicity of SARS-CoV-2 main protease (Mpro) expression in yeast under conditions that enforce mitochondria-dependent aerobic metabolism. Our results showed that Mpro expression was highly toxic and significantly impaired yeast growth. Pronounced changes in the morphology and mitochondrial function were observed, indicating that mitochondrial pathways are exceptionally sensitive to Mpro activity. These results provide insights that may be relevant for understanding the effects of Mpro in more complex eukaryotic systems.